The professional development features of higher education institutions lecturers - Батиченко, С.; Кривець, Ольга Олександрівна (Київський національний університет імені Тараса Шевченка, 2021)
In today’s world, an adult faces many challenges, which determine the need to learn continuously, improve one’s skills, and sometimes even change one’s profession. The concept of adult education has been developed in the view of a number of issues, namely, natural aging of the population and demographic crisis; rapid external labor migration; labor market imbalance associated with a significant number of workers with higher education and shortage of workers; modern competencies by people aged “45+” insufficient for successful employment and active participation in public life; lack of state policy on adult education in Ukraine during all the years of independence, in contrast to the EU policy and practice in this area. Due to the lack of open, complete and reliable information on adult education, as well as its components, namely the professional growth of employees in general and lecturers in particular, sociological research on these issues. The issues of improving the professional growth of employees, the peculiarities of the organization of the process of professional growth of employees, self-education and the most effective forms of adult education are revealed. As a result of a sociological study, it was found that employees are ready for self-education and professional growth, but it should be supported by employers and officials at various levels. Investigating the issues of professional growth of lecturers of higher education establishments, a sociological study was conducted in 2020 and 2021. The study has revealed the issue of compliance with legislation and actual implementation of conditions for professional growth of lecturers; dependence on advanced training and career growth; self-education and skills gained as a result, as well as a rating of soft skills; self-education for development of soft skills; features of the combination of family and professional duties; satisfaction with working conditions and subsequent desire to change one’s job. The study has established that a high percentage of respondents are committed to advanced training in accordance with the legislation of Ukraine; half of the respondents believe that there is no correlation between one’s professional growth and career growth; the share of lecturers involved in self-education for development of soft skills is growing every year; a third are dissatisfied with working conditions, and half of the respondents are about to change their jobs.

В сучасному світі перед дорослою людиною постає безліч викликів, які обумовлюють необхідність постійно навчатись, підвищувати свою кваліфікацію, іноді навіть змінювати свою спеціальність. Розроблення концепції освіти дорослих зумовлено низкою проблем, а саме: природним старінням населення та демографічною кризою; стрімкою зовнішньою трудовою міграцією; дисбалансом на ринку праці, що пов’язаний зі значною кількістю працівників з вищою освітою і браком робітничих кадрів; недостатністю для успішного працевлаштування й активної участі у суспільному житті рівня володіння сучасними компетенціями особами вікової категорії “45+”; відсутністю протягом усіх років незалежності державної політики з навчання дорослих в Україні, на відміну від сталої в ЄС політики та практики у цій сфері. У зв’язку з відсутністю відкритої, повної та достовірної інформації щодо освіти дорослих, а також її складових, а саме – професійного розвитку працівників загалом і викладачів зокрема, проведені соціологічні дослідження даних питань. Розкриті питання підвищення професійного розвитку працівників, особливостей організації процесу професійного розвитку працівників, самоосвіта та найефективніші форми навчання дорослого населення. У результаті соціологічного дослідження виявлено, що працівники готові до самоосвіти та професійного зростання, але при цьому потрібно, щоб була підтримка з боку роботодавців, чиновників різних рівнів. Досліджуючи питання професійного розвитку викладачів закладів вищої освіти, проведено соціологічне дослідження у два етапи: у 2020 та 2021 р. Під час дослідження розкрито питання відповідності законодавчим нормам і фактичному виконанні стосовно підвищення кваліфікації викладачами; залежністю підвищення кваліфікації та кар’єрного зростання; самоосвіта й навички, які в результаті отримали, а також рейтинг гнучких навичок; самоосвіта для розвитку гнучких навичок (softskills); особливості поєднання сімейних і професійних обов’язків; задоволення умовами праці та, як результат – прагнення змінити роботу. Встановлено, що високий відсоток респондентів відповідально ставиться до підвищення кваліфікації відповідно до законодавства України; половина респондентів уважає, що відсутня кореляція між підвищенням кваліфікації та кар’єрним зростанням; щороку зростає відсоток викладачів, які займаються самоосвітою для розвитку гнучких навичок (softskills); третина не задоволена умовами праці, а половина замислюється про зміну роботи.
Особливості професійного розвитку викладачів закладів вищої освіти
About the statement of the professional standard on group of professions “Teachers of institutions of higher education”. 610 §4, 5 (2021) Derzhavna sluzhba statystyky Ukrayiny, 2021, September [State statistics service of Ukraine]. Retrieved from http://www.ukrstat.gov.ua/druk/ publicat/kat_u/2021/zb/06/zb_rpn21_ue.pdf Kolyshko, R., Lazorenko, O. (2018) Yakoyu maye buty polityka navchannya doroslykh v Ukrayini? Analitychna zapyska. [What should be the policy of adult education in Ukraine?]. Retrieved from https://www.civic-synergy.org.ua/wpcontent/uploads/2018/04/Navchannya_doroslyh_v_Ukrayi ni.pdf. (Іn Ukrainian). Kostyuchenko, O. (2021). Navchannya protyahom zhyttya yak sposib zberezhennya i rozvytku trudovoho potentsialu Ukrayiny: Suchasni vyklyky ta priorytetni napryamy zberezhennya ta rozvytku trudovoho potentsialu Ukrayiny [Lifelong learning as a way to preserve and develop the labor potential of Ukraine: Current challenges and priority areas for the preservation and development of labor potential of Ukraine] Kyiv, KNU. (Іn Ukrainian). Mykytyuk, O., Petrenko, K. (2021). Suchasni tendentsiyi formuvannya osvitn’oho statusu doroslykh : Suchasni vyklyky ta priorytetni napryamy zberezhennya ta rozvytku trudovoho potentsialu Ukrayiny [Modern tendencies of formation of educational status of adults : Current challenges and priority areas for the preservation and development of labor potential of Ukraine] Kyiv, KNU. (Іn Ukrainian). Zakon Ukrayiny pro vyshchu osvitu (2014) [On Higher Education] 1556-VII § 10 57 et. seq. Sakharuk, I. (2021). Rol’ sotsial’noho dialohu u prosuvanni kontseptsiyi navchannya protyahom zhyttya: pidkhody Mizhnarodnoyi orhanizatsiyi pratsi: Suchasni vyklyky ta priorytetni napryamy zberezhennya ta rozvytku trudovoho potentsialu Ukrayiny. [The role of social dialogue in promoting the concept of lifelong learning: the approaches of the International Labor Organization: Current challenges and priority areas for the preservation and development of labor potential of Ukraine] Kyiv, KNU. (Іn Ukrainian). Tytarenko, D. V. (2015). Dzherel’na baza upravlinnya osvitoyu doroslykh v Ukrayini [Source base of adult education management in Ukraine]. Retrieved from http://www.kbuapa.kharkov.ua/e-book/db/2015-2/ doc/3/01.pdf.(Іn Ukrainian).
Keywords: освіта дорослих; освіта впродовж життя; професійний розвиток; самоосвіта; softskills; adult education; lifelong learning; professional growth; self-education; soft skills